Economic crimes and their social reflections: A field study - MUHAMMED, HASAN; MAJEED, AZHAR (Al-Adab Journal, 2024)
The research (economic crimes and their social repercussions, a field study) emphasized the identification of economic crimes and the extent of their impact on Iraqi society through their impact on joints and social aspects such as social security, food security, health security, and other social aspects. This study also sought to identify solutions that lead to reducing To reduce this crime and show the seriousness of this crime, the researcher relied on the social survey method on a random, intentional sample of 200 respondents who worked at the border crossings in Diyala Governorate (Al-Mundhiriya border crossing, Mandali border crossing). The researcher used the questionnaire as a means of collecting data.